2022
DOI: 10.3389/fcvm.2022.824467
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Two-Dimensional Speckle-Tracking Echocardiography in Patients Undergoing Surgical Ventricular Restoration

Abstract: ObjectivesParameters of left ventricular (LV) mechanics, obtained from speckle-tracking echocardiography (STE), were found to be of prognostic value in patients with heart failure and those who underwent cardiac surgery. This study aimed to assess the value of STE in patients scheduled to undergo surgical ventricular restoration (SVR).MethodsA total of 158 consecutive patients with baseline STE who underwent SVR due to an LV anteroapical aneurysm were included in the analysis. Preoperative longitudinal STE par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…LV GLS assessed by the 2D speckle-tracking strain analysis is the ratio of the maximal change in myocardial longitudinal length in systole to the original length and is capable to unmask subtle myocardial dysfunction [ 9 , 33 ]. Furthermore, it has been shown that it also can predict cardiac adverse events [ 9 , 33 , 34 ]. Our study confirmed this issue.…”
Section: Discussionmentioning
confidence: 99%
“…LV GLS assessed by the 2D speckle-tracking strain analysis is the ratio of the maximal change in myocardial longitudinal length in systole to the original length and is capable to unmask subtle myocardial dysfunction [ 9 , 33 ]. Furthermore, it has been shown that it also can predict cardiac adverse events [ 9 , 33 , 34 ]. Our study confirmed this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we complementarily employed echocardiography to evaluate the LV diameters, systolic function and severity of MR. The profound analysis of further echocardiographic data in the represented patient cohort, especially the prognostic role of speckle-tracking echocardiography (LV global longitudinal and basal longitudinal strain), is presented separately ( 21 ).…”
Section: Discussionmentioning
confidence: 99%